2001
DOI: 10.1007/s002400000154
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine phosphorylase/platelet-derived endothelial cell growth factor (PD-ECGF) associated with prognosis in renal cell carcinoma

Abstract: We investigated the correlation between thymidine phosphorylase (TP)/platelet-derived endothelial cell growth factor (PD-ECGF) expression, angiogenesis, and prognosis in renal cell carcinoma (RCC) patients. We prepared paraffin block specimens from 56 postradical nephrectomy RCC patients. The preparations were immunohistochemically stained using anti-CD34 antibody and anti-TP antibody. Angiogenic findings were evaluated based on both microvessel density (MVD) and renal arteriography findings as classified by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
1
24
0
Order By: Relevance
“…The median ( SD , range) diameter for all 54 tumours was 7.5 (2.85, [3][4][5][6][7][8][9][10][11][12][13][14] cm; a large tumour was defined as having a diameter of > 7 cm. The MVD was significantly different between the 28 large and 26 small tumours ( P = 0.005; Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median ( SD , range) diameter for all 54 tumours was 7.5 (2.85, [3][4][5][6][7][8][9][10][11][12][13][14] cm; a large tumour was defined as having a diameter of > 7 cm. The MVD was significantly different between the 28 large and 26 small tumours ( P = 0.005; Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Yoshino et al [2] and Paradis et al [3] reported that patient survival was significantly correlated with microvessel density (MVD), while others [4][5][6] reported that MVD did not correlate with metastasis. By contrast, others [7][8][9] reported that a higher MVD was associated with longer patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…12 Suzuki et al also reported that MVD had no predictive value for cancerspecific survival. 13 Slaton et al found no correlation between MVD and metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…12 and Suzuki et al . 13 reported MVD had no predictive value for cancerspecific survival. Similarly, Slaton et al .…”
Section: Introductionmentioning
confidence: 95%
“…For most of solid tumours, microvessel density (MVD) correlates with poor prognosis. However, MVD remains a controversial prognostic predictor for RCC (Kirkali et al, 2001;Sabo et al, 2001a;Suzuki et al, 2001;Dekel et al, 2002;Kinouchi et al, 2003;Yildiz et al, 2008;Qian et al, 2009), a significant contributory factor being that blood vessels in RCC may be regarded as being monolithic in structure and function, which might not accurately reflect the functional diversity based on microvessel differentiation and location. Mature blood vessels are usually covered by pericytes, and pericyte coverage is regarded as an indicator of vascular maturation (Gerhardt and Semb, 2008).…”
Section: Hai-lun Zhan Xin Gao* Xiang-fu Zhou Xiao-yong Pu De-juanmentioning
confidence: 99%